Linear cavity optical-feedback cavity-enhanced absorption spectroscopy with a quantum cascade laser. - Bergin, A; Hancock, G; Ritchie, G; Weidmann, D (2013)
A cw distributed feedback quantum cascade laser (DFB-QCL) coupled to a two-mirror linear optical cavity has been used to successfully demonstrate optical-feedback cavity-enhanced absorption spectroscopy (OF-CEAS) at 5.5 μm. The noise-equivalent absorption coefficient, α(min), was 2.4×10(-8) cm(-1) for 1 s averaging, limited by etalon-fringing. The temporal stability of the instrument allows NO detection down to 5 ppb in 2 s.